Sensory Evolution on the Threshold : Adaptations in Secondarily Aquatic Vertebrates. - Thewissen, J. G. M. (Berkeley : University of California Press, 2008)
Ranging from crocodiles and penguins to seals and whales, this synthesis explores the function and evolution of sensory systems in animals whose ancestors lived on land. It explores the dramatic transformation of smell, taste, sight, hearing, and balance that occurred as lineages of reptiles, birds, and mammals returned to aquatic environments.
Cover; Title; Copyright; Contents; Contributors; 1. Introduction: On Becoming Aquatic; Chemical Senses; Vision; Hearing; Balance; Mechanoreception; Magnetoreception and Electroreception; Index.
Print version record.
Includes bibliographical references and index.
English.
JSTOR
Keywords: Aquatic animals -- Sense organs; Aquatic animals -- Adaptation; Sense organs -- Evolution; Faune aquatique -- Organes des sens; Faune aquatique -- Adaptation; Organes des sens -- Évolution.; SCIENCE -- Life Sciences -- Zoology -- General; Aquatic animals -- Adaptation; adapting to their environment; anatomy; animal senses; animal sensory systems; astonishing transition; botany and ecology; crocodiles; electroreception; evolutionary adaptation; magnetoreception; mechanoreception; natural sciences; neurobiology; penguins; physiology; seals; sens organs; sensory biology; theory of evolution; whales